Pathogenicity of Phytophthora alni complex and P. plurivora in Alnus glutinosa seedlings. Issue 2 (22nd July 2016) - Zamora‐Ballesteros, C.; Haque, M. M. U.; Diez, J. J.; Martín‐García, J.
Summary: The ecological importance of riparian forests is well known. However, these forest habitats have been disturbed by human activities over the past century as a result of the introduction of flow regulations. Mortality of the riparian alder population caused by Phytophthora has become an important issue in Europe in the past two decades. The main objective of this study was to examine the pathogenicity of the Phytophthora alni complex ( P. x alni, P. uniformis and P. xmultiformis ) and P. plurivora in Alnus glutinosa seedlings. Phytophthora alni complex has traditionally been identified as the main causal agent of alder decline; however, in this study, P. plurivora was found to cause as much damage in inoculated seedlings as P. alni complex. In fact, Spanish isolates of P. x alni caused mortality rates of ca. 30%, whereas P. plurivora killed ca. 50% of seedlings. Likewise, there were no differences between P. x alni ‐ and P. plurivora‐ inoculated seedlings in either the length of lesion or biomass allocation. The pathogenicity of the species within P. alni complex did not differ significantly. The findings confirm that P. plurivora, which is one of the most common species of Phytophthora found in European nurseries, is highly pathogenic to alder seedlings. Urgent implementation of measures to prevent the risk of spread of the pathogen from nurseries to natural ecosystems is required. Further studies are required to clarify the role that P. plurivora is playing in alder decline both individually and in combination with P. alni complex.